Penguatan Moralitas Digital dalam Kehidupan Masyarakat melalui Penerapan Nilai-Nilai Islam pada Penggunaan Media Sosial di Era Teknologi Modern - Hendrik Maulana; Supriyadi Supriyadi; Rusiani Husnul Fadilla; Dannu Sudibyo; Rifan Gunawan; Ismail Mubarok (International Forum of Researchers and Lecturers, 2026)
Social media has become an essential part of modern society, shaping how individuals communicate, share information, and express opinions in daily life. However, uncontrolled use of social media may weaken behavior and communication ethics, especially through misinformation, cyberbullying, hate speech, and impolite interaction in digital spaces. This study aims to examine how Islamic values can serve as a foundation for developing digital morality in social media usage. The research applied a qualitative descriptive approach through a literature study by reviewing sources related to digital ethics, Islamic education, and moral teachings. The findings reveal that honesty, responsibility, politeness, verification, and spiritual awareness are key Islamic values that can guide users toward wiser and more accountable online behavior. These values encourage users to verify information before sharing, avoid harmful speech, respect others, and maintain self-control in digital communication. The study concludes that strengthening digital morality requires not only technological competence but also the integration of spiritual values to create a healthier, ethical, and responsible digital environment for society in contemporary life today.